Screens or MP4s: Acquiring Clinical Competencies Through the Use of e-OSPEs in Occupational Therapy - Lizahn Gracia Cloete; Lee-Ann Juliana; Lana van Niekerk (Scholarworks @ WMU, 2018)
The assessment of clinical competence of undergraduate students is a crucial part of higher education training in occupational therapy. The use of online objective standardized practical examinations (e-OSPEs) was piloted as a technological innovation to determine student learning needs. An action research framework with four phases was used. Descriptive statistics in the form of frequency tables and percentages were used to report survey results. The students had multiple practice opportunities before uploading their best attempt. Thirty participants completed a 12-item survey. The results were analyzed using descriptive analysis and presented by means of statistical graphs. Peer assessment facilitated experiential learning. Twenty-seven out of 30 students (90%) felt adequately prepared for submitting their video clips. The students found the opportunity to practice the skills multiple times before uploading the e-OSPEs helpful. The students experienced an increase in workload when the e-OSPEs were due during clinical placement and examination periods. Additional resources are needed for creating initial infrastructure for implementing e-OSPEs. The findings of this study could inform the planning of future online assessment practices of clinical competencies in occupational therapy. Identifying, formulating, and assessing competence standards electronically may guide occupational therapy practitioners' work with diverse patients and populations.